PERFORMANCE ANALYSIS OF THE SHALLOT SUPPLY CHAIN IN SAMOSIR REGENCY, NORTH SUMATRA PROVINCE - Kimberly Febrina Kodrat; Hasan Sitorus (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
This research aims to analyze the performance of the shallot supply chain in Samosir Regency. Place and Time of Research This research was conducted in Samosir Regency, North Sumatra Province. Data Collection and Analysis Analysis of the Condition of the Shallot Supply Chain The condition of the shallot supply chain is discussed descriptively following the FSCN (Food Supply Chain Network) discussion framework developed by Van der Vorst. The research results show that shallot supply chain activities in Samosir Regency are based on a food supply chain networking model where fluctuating prices and weather are the main inhibiting factors in supply chain activities starting from product availability to delivery. Measuring the performance of the shallot supply chain using the Supply Chain Operations Reference (SCOR) method has not shown optimal results on all indicators such as delivery performance, standard compliance and conformity with standards. Judging from the profit shares of producers, collectors and retailers, they differ from each other, this reflects the unequal profits of each trading system so that the trading system in this area is not yet efficient. In general, the shallot trading system in this village is not yet efficient. It is a good idea for farmers themselves to sort and sort small, medium and large shallots. So that the selling price can also increase and be more profitable.